Glúten info: desenvolvimento de ferramenta móvel de busca por serviços sem glúten em Belém - SANTOS, Giovana Sousa dos (2023)
Introduction: One of celiac's daily challenges is to find places (which provide services and products) that meet their dietary needs (gluten-free products and preparations). The mapping of gluten-free places can prevent food transgressions, improve social life in order to make a better quality of life. Objective: To develop and validate an application containing information about spots and gluten-free services in the metropolitan area of BelémPA. Methods: This was a methodological study based on the development of a mobile application. The development of the tool included four steps: Analysis, Development and Design, Low Quality Model Development with Validation and High Quality Model Development with Implementation. The research was approved by the Ethics Committee of the Federal University of Pará with CAAE 03187418.0.0000.0018 and had 40 participants. Results: The app is divided into six sections, Where to eat, Where to buy, Where to host, Courses and Events, Celiac Network and Contact. In the Where to eat section, 7 items were include, using information such as name and characterization of the services offered, physical addresses, social networks and opening hours of these items. The same information was considered for the section Where to buy (with 11 places) and Where to stay (no spots found) section. In the Courses and Events section, we considered the event date, location, physical address, event website and organization email. The Celiac Networks page listed the main celiac networks and associations in the country, and found 10 associations. For this section, we considered the area of expertise, social networks and contact information. In the Contact section, forms of communication were made available for complaints and suggestions from users. When applied online form, 93% of celiac respondents said they were very interested in the application proposal. Regarding the assessment of the degree of user satisfaction in terms of layout, 73% answered very satisfied. Regarding the information provided in the app, 75% said they were very satisfied with the content available. Conclusion: The pilot application developed was well accepted and evaluated by the target audience and can be considered an important tool to facilitate the daily lives of people with gluten-related disorders.